STRATEGI DALAM MENINGKATKAN LOYALITAS NASABAH DI BANK SYARIAH INDONESIA KCP LUMAJANG IMAM BONJOL - Eristiana Choirun Nisa; Siva Indana Arisanti; Ahmad Fauzi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Abstrak. This research aims to explore strategies for increasing customer loyalty at Bank Syariah Indonesia KCP Lumajang Imam Bonjol. Against the backdrop of increasingly fierce competition in the sharia banking sector, this research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with bank management and several loyal customers, as well as direct observation of bank services. The research results show that implementing sharia values, improving service quality, sharia product education, and good personal relationships are the main factors in building customer loyalty. These strategies not only increase customer trust but also strengthen long-term relationships between banks and customers. This research provides insight for Islamic bank management to design more effective policies in maintaining customer loyalty amidst the challenges of the modern banking industry.